Research progress of gut microbiome and diabetic nephropathy - Chenling Chu; Tapas Ranjan Behera; Ying Huang; Wenhui Qiu; Jiayi Chen; Quanquan Shen; Quanquan Shen (Frontiers in Medicine)
Diabetic nephropathy is an important complication of diabetic microvascular injury, and it is also an important cause of end-stage renal disease. Its high prevalence and disability rate significantly impacts patients’ quality of life while imposing substantial social and economic burdens. Gut microbiota affects host metabolism, multiple organ functions, and regulates host health throughout the life cycle. With the rapid development of technology, researchers have found that gut microbiota is closely related to the progression of diabetic kidney disease. This review explores the role of gut microbiome in diabetic nephropathy summarizing proposed mechanisms of progression and focusing on microbial metabolites, intestinal barrier disruption, inflammation, filtration barrier damage and renal fibrosis. This review also examines the mechanism and limitations of current treatments, including drugs, fecal microbiota transplantation, and lifestyle changes, offering new perspectives on prevention and treatment.